Dragon of the red dawn - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series. Merlin missions, 2017)
When Merlin is weighed down by sorrows, Jack and Annie travel back to feudal Japan to learn one of the four secrets of happiness.